Synthesis And Characterisation Of Silver Nanoparticles Using Vernonia cinerea Aqueous Extract And Their Cytotoxic Activity Against Kasumi-1 Cell Line - Mohamad Zani, Radhiyatul Akma (2016)
Nanotechnology has gained attention due to their wide applications in various areas such as cancer diagnosis and therapy. Production of silver nanoparticles (AgNPs) using plant extracts is safer and cost-effective compared to chemical and physical methods. In this study, AgNPs were produced using 1:5, 1:10 and 1:20 ratios of Vernonia cinerea (V. cinerea) aqueous extract and silver nitrate solution. The mixtures were incubated for 24 hour at 40 ˚C water baths. The formation of silver nanoparticles was monitored for colour changes and characterized by UV-Vis spectroscopy followed by transmission electron microscopy (TEM) and zeta potential analyses.